Pentingnya implementasi pendidikan multikultural di sekolah - Hanum, Farida (Cakrawala Pendidikan, 2006)
The Indonesian society is a multicultural one consisting of a variety of ethnic groups with a variety of languages and cultures of thir own. It implies not only a richness and strength but also a potential for conflict. Such potential is also implied in the contry's relationships with other countries; in the communication between the peoples concernet, misundaerstandings may results due to differences in culture.To understand and respond to the differences peacefully, it is important for the peoples concernet to have multicultural education, formally or informally. Such education can be integrated into some relevant lessons in class. Multicultural education should not only teach ethnical cultural symbols, such as, tranditional houses, dress, dances, or songs; but also invlve transformation and action.In the implementation of such multicultural education, there must be chalenges coming especially from teachers and other educators at schools who underestimate multicultural education while the educational resources involved need to be free from bias and stereotyping rlated to ethnical, relegious, gender, social class, anad ubarn-rural )or cityh-village) differences.Â